Employment effects of minimum wage changes across regions, age groups, and sectors - Aleksandra Majchrowska; Pawel Strawinski (Journal of Banking and Financial Economics (JBFE), 2023)
Increases in minimum wages in many developed and developing economies in recent years raise the question of whether and how they impact employment. We analyze the employment effects of minimum wage increases for different age groups of workers simultaneously. We construct a panel using three-dimensional cells formed by three age groups, two economic sectors, and 16 regions, separately for each year. We use individual data on employee and employer characteristics from the Structure of Earnings Survey and aggregated data from the Local Data Bank in Poland. The research period covers 2006-2020. Our results confi rm the differences in employment elasticity for different groups of workers. We discover latent heterogeneities with regions simultaneously experiencing both negative and positive employment effects of minimum wage changes for different groups of workers and sectors. Negative employment effects are observed mostly for youths, positive employment effects are predominant in the groups of workers aged 50 and over. The employment reaction to changes in the minimum wage is the result of a combination of regional labor market features. Negative employment effects are more likely in areas with larger proportion of workers in the private sector, in industries in which it is more diffi cult to increase the prices of goods or services produced, and where small fi rms are widespread. The results show that previous analyses at the aggregated level might underestimate the employment effects of the minimum wage. The results also show that the overall minimum wage effects cannot be easily predicted by policymakers.
Keywords: J21; R23; J31; J38; 330; employment elasticity; minimum wage; regional labor markets; multidimensional panel analyses; intra-regional differences; Poland